CÓMO INFLUYEN LA CONDUCTA DE LOS EMPLEADOS, LA SATISFACCIÓN DE LOS CLIENTES Y EL INTERÉS DE INVERTIR DEL ACCIONISTA EN LA EXPANSIÓN Y RENTABILIDAD DE LAS EMPRESAS COMERCIALES - Márquez Guevara, Luis (2006)
One way to improve the growth and profits of a corporate is having a vision of business as a pleasant place to work, an interesting place to buy and an interesting place to invest .This trilogy shows that if the worker behavior to the customer is correct, if the client gets satisfied with the product that the company sells, because it covers adequately his needs; and if enhance the profits of shareholders, we are facing an developed and profitable corporate. The results of this trilogy are known through a Balanced Scorecard by a properly management control, this corrective measures that will permit to keep in favorable ways the application of this trilogy.